Synthesis, comprehensive in silico studies, and cytotoxicity evaluation of novel quinazolinone derivatives as potential anticancer agents - David S. A. Haneen; Abdelaal A. Abdalha; Musaab M. Alkhatib; Mahmoud Kamal; Ahmed S. A. Youssef; Wael S. I. Abou-Elmagd; Sandy S. Samir (Scientific Reports)
Abstract Quinazolinone derivatives exhibit significant synthetic and biological properties, making them valuable candidates for anticancer drug development. In this study, we synthesized novel quinazolinone derivatives via reactions of the previously unreported 4H-benzoxazin-4-one derivative (2) with various nitrogen nucleophiles, such as hydrazine hydrate and ammonium acetate, which yielded hydrazide and quinazolinone derivatives (3–6). Further modifications were achieved through reactions with carbon electrophiles and carbonyl compounds (e.g., phthalic anhydride, phenyl isothiocyanate, potassium cyanate, and pyrazole carbaldehyde), resulting in an expanded library of novel quinazolinone derivatives (7–15). The structures of all synthesized compounds were confirmed by spectroscopic and microanalytical techniques. In vitro cytotoxicity evaluations (mean IC50 ± SE, n = 3) revealed promising anticancer activity, with compounds 3 and 5 demonstrating the highest efficacy. To gain deeper mechanistic insights, molecular docking and molecular dynamics simulations were performed against key cancer-related targets, including Topoisomerase II, VEGFR2, c-Met, EGFR, and Estrogen Receptor Alpha. The combined experimental and computational findings suggest that these quinazolinone derivatives hold significant potential as novel anticancer agents, justifying further biological investigations and structural optimizations.